Validity and reliability of Turkish version of the craving experience questionnaire in the assessment of cigarette smoking. (3rd September 2021) - Kılıç, Sema; Tan, Makbule Neslişah; Mevsim, Vildan
ABSTRACT: Background : Intense desire (craving) for smoking is an essential feature of a tobacco use disorder. The aim of this study was to cross-culturally translate and validate the Turkish version of Craving Experience Questionnaire (CEQ-T).Methods : Forward-backward-forward translation method was used to translate. The methodological study sample included 744 current daily tobacco smokers. The validity of the scale was tested with construct (through exploratory factor analysis) validity and criterion-related validity. The Fagerström Test for Nicotine Addiction (FTND) and Substance Craving Scale (SCS) were used for criterion-related validity. Cronbach's alpha, Pearson product-moment correlation coefficient and independent samples t-test were used to evaluate the reliability of the scale by internal consistency and test–retest method.Results : The construct validity showed three factors in each form that explain 77.4% of total variance for CEQ-T-Strength and, 78.4% for CEQ-T-Frequency. There was a significant positive correlation between CEQ-T and FTND and SCS. Cronbach's alpha internal consistency coefficient was 0.87 for CEQ-T-Strength, and 0.83 for CEQ-T-Frequency. In test–retest reliability, the correlation coefficient was 0.88 for CEQ-T-Strength and 0.89 for CEQ-T-Frequency.Conclusion : The Turkish version of CEQ is a valid and reliable measuring tool that can be used to assess the craving in Turkish smokers.